To Combine or Not to Combine Physical Therapy With tDCS for Stroke With Shoulder Pain? Analysis From a Combination Randomized Clinical Trial for Rehabilitation of Painful Shoulder in Stroke - Andressa de Souza, Janaina; Ferrari Corrêa, João Carlos; Marduy, Anna; Dall'Agnol, Letizzia; Gomes de Sousa, Maria Helena; Nunes da Silva, Victor; Alves, André Barreto; Silva, Soraia Micaela; Fregni, Felipe; Corrêa, Fernanda Ishida (Frontiers in Pain Research, 2021)
Purpose: Transcranial Direct Current Stimulation (tDCS) is an intervention that seems to be an ideal tool to enhance the effects of rehabilitation therapies given it facilitates generation of plasticity in the stimulated brain area. In stroke this strategy has been highly utilized; however, the results have been mixed. In this trial we have evaluated the analgesic and functional effects of Transcranial Direct Current Stimulation (tDCS) combined with physiotherapy in stroke survivors with shoulder pain. Methods: Twenty-six stroke surviving adults with shoulder pain received 10 sessions of passive mobilization and performed upper limb exercises using a cycle ergometer, combined with active or sham tDCS. The intensity of pain in the hemiplegic shoulder was measured using the Visual Analog Scale (VAS); secondary outcomes were the level of motor impairment, handgrip strength, range of motion, motor function of the upper limbs, and quality of life (QOL) assessed before and after 10 sessions and 1 month after the end of the treatment. Results: A clinically important pain reduction (3 points) was found in both groups and was maintained at follow-up; there was no significant difference between groups (p = 0.3). Similarly, the shoulder range of motion improved, motor function and quality of life improved showed no significant differences between groups. One result that needs to be underscored is that both groups had a significant effect size toward improvement in all of these outcomes. Conclusions: We discuss in this study that tDCS is not a useful combination strategy when the physical therapy has a large effect by itself and we also review other negative trials of combined therapy under this framework of ceiling effect of the main physical therapy. Trial registry: Trial registration: Brazilian Registry of Clinical Trials, RBR-8F5MNY (http://www.ensaiosclinicos.gov.br/rg/RBR-8f5mny/). Registered on June 2, 2017. Beginning of the recruitment of the volunteers: august, 2017.